STUDI LITERATUR ANALISIS KESULITAN MEMBACA PERMULAAN SISWA KELAS II SEKOLAH DASAR - Anggraeni, Delia Sri; Siti Nurkamilah2; Risma Nuriyanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the forms of early reading difficulties and their contributing factors in second-grade elementary school students. The method used in this study is a literature study, namely the activity of collecting and processing research data. This research data was obtained from several articles previously obtained from Google, Google Scholar, and other websites with a period of 2020-2026. Data were analyzed through data reduction, data presentation, and drawing conclusions. The results of the analysis revealed that the forms of early reading difficulties experienced by students include difficulty spelling syllables, difficulty distinguishing letters that are almost the same shape (such as b-d, p-q, m-n), difficulty reading diphthongs and double consonants (digraphs), difficulty understanding punctuation, and low reading comprehension. The factors causing these difficulties are divided into two: internal factors such as low motivation and interest in learning children and external factors such as the learning process and inadequate infrastructure.